Mapping and Trends of Midwifery Research in Indonesia - Adnani, Qorinah Estiningtyas Sakilah; Melani, Margareta; Richa, Fadhila Tsania; Argaheni, Niken Bayu (FORIKES, 2026)
In Indonesia, the growth of midwifery studies reflects broader efforts to strengthen the health system and enhance professional capacity. This study provides a quantitative mapping of scientific publications related to midwifery in Indonesia using several key parameters, including author productivity, citation frequency, country contributions, document types and subject areas, institutional affiliations, author keywords, and density visualization. Data were collected from indexed scientific publications and systematically examined to identify trends and patterns in midwifery studies in Indonesia. The findings indicate variations in author productivity, with several contributors demonstrating notable influence in the field. Citation patterns reflect the level of recognition and impact of published work within the scientific community. Country distribution highlights Indonesia’s contribution to global midwifery knowledge. Analysis of document types and subject categories offers insight into the scope and focus of midwifery studies, while institutional affiliation mapping identifies key centers of scholarly activity. Author keyword analysis and density visualization further illustrate thematic development and emerging areas within the field. These findings provide valuable insights for researchers, practitioners, and policymakers in guiding future directions and strengthening the development of midwifery studies in Indonesia.Keywords: bibliometric; midwifery; maternal health; scientific publications; Indonesia.